The Relationship Between Impulsivity Level and Neutrophil / Lymphocyte Ratio, Platelet/ Lymphocyte Ratio and Mean Platelet Volume in Individuals Diagnosed with Gambling Disorder - Yildiz, Sevler; Kılıçaslan, Aslı Kazğan; Tabara, Muhammed Fatih; Atmaca, Murad (My University, 2021)
Aim: Gambling disorder (GD) is a mental illness with an increasing frequency in society that characterized by the urge to gamble despite negative consequences and desire to quit. In this study, we aimed to examine the mean platelet volume (MPV), neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR) and the relationship between these values and impulsivity in patients with GD.Material and Method: 42 patients diagnosed with gambling disorder and 42 healthy controls were included in this study. Sociodemographic data form, Barratt Impulsivity Scale Short Form (BIS-11-SF) were administered to all participants, and then a complete blood count was requested from these individuals. NLR, PLR and MPV were measured according to complete blood count.Results: The mean BSI-11-SF total score of the patient group was found to be statistically significantly higher than the control group (p <0.05). It was found that while the motor impulsivity scores of GD patients increased, the MPV values significantly decreased (r=-0.33, p = 0.03). There was no significant difference between the patient and control groups in terms of NLR (p = 0.288), PLR (p = 0.377) and MPV (p = 0.883) values. In addition, in the patient group, there was a weak negative correlation between age and motor impulsivity score and a weak negative correlation between motor impulsivity score and MPV (r=-0.33, p=0.03), (r=-0.31, p=0.04).Conclusion: It was concluded that an individual’s diagnosis with gambling disorder had a high level of impulsivity, but there was no relationship between gambling and complete blood count parameters. Further studies are needed to explain the etiopathogenesis of gambling disorder.
Keywords: Impulsivity; Gambling Disorder; neutrophil / lymphocyte; platelet/lymphocyte; platelet volüme